Evaluación de la extracción soxhlet para la obtención de taninos a partir de la borra de café (2023)
Initially, a bromatological analysis is carried out on the sample, in this case coffee grounds, the tests are carried out under two regulations which are AOAC and ISO respectively, in which physicochemical parameters are determined such as humidity (7.33%), ash ( 0.33%), total solids (92.67%), protein (11.60%), nitrogen (1.86%) and finally its sugar profile (<0.1%). Although there is no specific test established for the extraction of this type of metabolites, the Soxhlet methodology will be used, which consists of the reflux of a solvent in the sample.